A customized scheme of crosstalk cancellation for operational transfer path analysis and experimental validation. (22nd December 2021) - Cheng, Wei; Chu, Yapeng; Lu, Jingbai; Song, Chao; Chen, Xuefeng; Zhang, Le; Wajid, Basit Ali; Gao, Lin
Highlights: ● A customized scheme of crosstalk cancellation method for OTPA is proposed. ● Customized scheme of crosstalk cancellation for various possible operating conditions can be flexibly constructed. ● Both efficiency and accuracy of OTPA are enhanced. ● Vibration source identification and major transfer path can be accurately identified. ● This study can benefit vibration monitoring and control of mechanical systems. Abstract: To overcome crosstalk effects in operational transfer path analysis (OTPA) for effective identification and evaluation of vibration transfer path contributions based on measured response signals, a customized scheme of crosstalk cancellation for OTPA is proposed in this paper, which flexibly adopts different crosstalk cancellation methods for different path stages, and quantitatively evaluates transfer path contributions with high accuracy and efficiency. Firstly, the fundamental theories of OTPA and two crosstalk cancellation methods, prior transmissibility function-based method and independent component analysis (ICA) based method, are introduced. Secondly, an OTPA model is constructed for the test bed with shell structures, and the effects of airborne path contributions on OTPA is also analysed. Thirdly, the proposed customized scheme is applied to the two-stage transfer path of the test bed, and the vibration path contributions are comprehensively evaluated and analysed. Generally, this study proposes a flexible crosstalk cancellation scheme of OTPA for complex mechanical systems, which can provide reliable evidences for vibration and noise reduction and control.